Synanthropic rodents and their ectoparasites as carriers of a novel haemoplasma and vector-borne, zoonotic pathogens indoors - Hornok, Sándor (Parasit Vectors, 2015)
BACKGROUND: Despite their close association with human dwellings, the role of synanthropic rodents in the epidemiology of vector-borne infections is seldom studied. The aim of the present study was to compensate for this lack of information, by the molecular investigation of vector-borne bacteria in peridomestic rodents and their ectoparasites. FINDINGS: Fifty-two rodents (mainly house mice and brown rats) were caught alive in buildings and checked for blood-sucking ectoparasites; followed by molecular analysis of these, together with spleen samples, for the presence of vector-borne agents. Haemoplasma infection was significantly more prevalent among brown rats, than among house mice. A novel haemoplasma genotype (with only 92-93% similarity to Candidatus Mycoplasma turicensis and M. coccoides in its 16S rRNA gene) was detected in a harvest mouse and a brown rat. Sporadic occurrence of Rickettsia helvetica, Anaplasma phagocytophilum, Borrelia burgdorferi s.l. and Bartonella sp. was also noted in rodents and/or their ectoparasites. CONCLUSIONS: These results indicate that synanthropic rodents, although with low prevalence, may carry zoonotic and vector-borne pathogens indoors.